The Smart Grid as an Application Development Platform - Koutitas, George; McClellan, Stan, 1963- (Artech House power engineering series., 2017)
This authoritative new resource explores the power grid from its classical role as a utility or service provider towards its new role as an application development platform. This book gives insight into the vision, problems and solutions, and risks of the smart grid model. The evolution of the power grid as it develops into an application-centric environment is explained in this book. This resource guides readers to better understand the primary motivation of the smart grid, and to explore how new technologies are creating a cleaner and more sustainable ecosystem for new business models to blossom. Key topics include the basics of electricity and the conventional grid structure, as well as the relationships between conventional economic models and emerging models based on transactive energy and the sharing economy.n nThis book presents the orchestration of smart grid technologies as they are transforming the utility sector toward a human-centric grid. Readers gain insight into how they are playing an active role in the operation of the utility business as well as in the transfer of electrons. This book demonstrates how the new smart grid is becoming a distributed system that supports decentralized services through modern trends and distributed system architectures. Readers learn how grid intelligence and energy production migrates to the edge of the network. This book explores how consumers are transformed to "prosumers" of energy and providers of critical data that are dramatically changing the relationship with the electric utility business in order to enable new applications and services.